2021
DOI: 10.1093/brain/awab148
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 neuropathology at Columbia University Irving Medical Center/New York Presbyterian Hospital

Abstract: Many patients with SARS-CoV-2 infection develop neurological signs and symptoms, though, to date, little evidence exists that primary infection of the brain is a significant contributing factor. We present the clinical, neuropathological, and molecular findings of 41 consecutive patients with SARS-CoV-2 infections who died and underwent autopsy in our medical center. The mean age was 74 years (38–97 years), 27 patients (66%) were male and 34 (83%) were of Hispanic/Latinx ethnicity. Twenty-four patients (59%) w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
353
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 310 publications
(387 citation statements)
references
References 46 publications
28
353
1
5
Order By: Relevance
“…It has been shown that the virus could possibly reach the olfactory bulb and the brainstem [40]. In this regard, recent reports have outlined the presence of SARS-CoV-2 viral proteins in the brainstem, which was not necessarily associated with the severity of neuropathological changes [14, 15, 40]. Moreover, multifocal microvasculature injuries were recently reported in the brain of patients who were infected with SARS-CoV-2 presenting mild to severe symptoms and who died later after viral infection resolution [14, 15].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown that the virus could possibly reach the olfactory bulb and the brainstem [40]. In this regard, recent reports have outlined the presence of SARS-CoV-2 viral proteins in the brainstem, which was not necessarily associated with the severity of neuropathological changes [14, 15, 40]. Moreover, multifocal microvasculature injuries were recently reported in the brain of patients who were infected with SARS-CoV-2 presenting mild to severe symptoms and who died later after viral infection resolution [14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, recent reports have outlined the presence of SARS-CoV-2 viral proteins in the brainstem, which was not necessarily associated with the severity of neuropathological changes [14, 15, 40]. Moreover, multifocal microvasculature injuries were recently reported in the brain of patients who were infected with SARS-CoV-2 presenting mild to severe symptoms and who died later after viral infection resolution [14, 15]. The injury was associated to punctate hypointensities, corresponding to congested blood vessels with surrounding areas of fibrinogen leakage, and areas of linear hypointensities, corresponding to microhemorrhages [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations